1995
DOI: 10.1002/ijc.2910600409
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the NF2 tumor‐suppressor gene and of chromosome 22 deletions in gliomas

Abstract: Recurrent deletions of chromosome fragments observed in neoplasms are thought to participate in tumor development through the inactivation of tumor-suppressor genes. In gliomas, the most frequent deletions involve chromosome arms 9p, 10q, 17p, 19q and 22q. We have analysed deletions of chromosome 22 in gliomas by studying loss of heterozygosity (LOH) at 8 microsatellite loci. LOH for this chromosome fragment was observed in 17/70 (24%) cases, most of them encompassing the region which encodes the gene altered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
5

Year Published

1996
1996
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 23 publications
0
22
0
5
Order By: Relevance
“…The LIMK1 gene was recently suggested to be one of the causal genes of Williams' syndrome [17]. The locus of the LIMK2 gene is close to that of the tumor suppressor gene NF2 (neurofibromatosis 2) [24], Since loss on 22q near to but outside the NF2 locus was detected in some cases of menigiomas, gliomas, ovarian carcinoma and colorectal cancers [25][26][27], inactivation of the LIMK2 gene may be linked to the tumorigenesis of these cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The LIMK1 gene was recently suggested to be one of the causal genes of Williams' syndrome [17]. The locus of the LIMK2 gene is close to that of the tumor suppressor gene NF2 (neurofibromatosis 2) [24], Since loss on 22q near to but outside the NF2 locus was detected in some cases of menigiomas, gliomas, ovarian carcinoma and colorectal cancers [25][26][27], inactivation of the LIMK2 gene may be linked to the tumorigenesis of these cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of heterozygosity on chromosome arm 22q occurs in approximately 20-30% of diffuse astrocytomas, regardless of malignancy grade, suggesting the presence of a tumor suppressor gene involved in early astrocytic glioma development (89)(90)(91)(92)(93). A recent report by Ino et al (89) has defined two minimal deletion regions on 22q.…”
Section: Chromosome 22mentioning
confidence: 99%
“…Although malignant gliomas often have LOH on chromosome 22, this finding does not translate into mutations in the NF2 gene. [14] Instead, mutations in the NF2 gene associated with spinal ependymomas are found with a higher frequency in these patients. The nature of the gene mutations in Turcot syndrome and TS have not been well defined enough to draw any inferences of their role in glioma oncogenesis.…”
Section: Relationship Between Hereditary Neurological Tumor Syndromesmentioning
confidence: 96%
“…They did not find any mutations in the astrocytomas but found a mutation in a spinal ependymoma. Hoang-Xuan, et al, [14] found loss of heterozygosity (LOH) in chromosome 22 in 17 of 70 gliomas (World Health Organization [WHO] Grades II-IV astrocytomas, oligodendrogliomas, and oligoastrocytomas). They screened the samples with LOH in chromosome 22 for the mutations in the NF2 gene and did not find any mutations, leading them to conclude that NF2 gene mutations are not important for astrocytoma and oligodendroglioma tumorigenesis.…”
Section: Neurofibromatosis Typementioning
confidence: 99%